Owners, external managers, and industrial relations in German establishments - Arnd Kölling; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2019)
Using data from the representative IAB Establishment Panel in Germany and estimating a panel probit model with fixed effects, this paper finds a negative relationship between the existence of owner-management in an establishment and the probabilities of having a works council or a collective bargaining agreement. We show that family firms which are solely, partially or not managed by the owners significantly differ in the presence of works councils and collective bargaining agreements. The probabilities of having works councils and collective agreements increase substantially if just some of the managers do not belong to the owner family. We argue that these differences cannot simply be attributed to an aversion of the owners against co-determination and unions but require taking account of the notion of socio-emotional wealth prevalent in family firms. In addition, our results support the idea that external managers mainly act as agents rather than stewards in family firms. – – Mit repräsentativen Daten des IAB-Betriebspanels und bei Schätzung eines Panel-Probit-Modells mit fixen Effekten finden wir eine negative Beziehung zwischen der Beteiligung von Eigentümern am Management eines Betriebes und den Wahrscheinlichkeiten für die Existenz eines Betriebsrates bzw. eines Tarifvertrages. Wir zeigen, dass Familienunternehmen, die ganz, teilweise oder gar nicht von Eigentümern geleitet werden, sich signifikant bezüglich des Vorhandenseins von Betriebsräten und Tarifverträgen unterscheiden. Die Wahrscheinlichkeiten für die Existenz eines Betriebsrates und einer Tarifbindung sind deutlich höher, wenn nur einige der Manager nicht zur Eigentümerfamilie gehören. Diese Unterschiede sollten nicht allein auf eine Aversion von Eigentümern gegen Mitbestimmung und Gewerkschaften zurückgeführt werden, sondern das in Familienunternehmen zu findende Konzept eines "sozial-emotionalen Reichtums" ist ebenfalls zu berücksichtigen. Zudem deuten unsere Ergebnisse darauf hin, dass sich externe Manager in Familienbetrieben eher als eigenständige Agenten und weniger als Interessenwahrer der Eigentümer verstehen.
Keywords: J53; M54; G32; 330; industrial relations; co-determination; works council; collective agreement; family firm; Germany